Comparison of Frequency of Post Caesarean Wound Infection with Amoxicillin Versus Ceftriaxone - Sadia Irum, Sheema Rahim, Seemab Zafar, Ayesha Afridi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cesarean delivery is a crucial factor in association with postpartum infection, there is a 5 to 20-timesmuch higher risk of getting an infection in contrast with a vaginal delivery. By not having prophylactic antibiotics, the rates of postpartum endometritis can reach 35 to 40%. This study was conducted to contrast the frequency of postoperative wound infection in patients receiving prophylactic amoxicillin vs. ceftriaxone. Methods: This Randomized Controlled Trial was conducted at the Department of Obstetrics & Gynecology, Ayub Teaching Hospital, Abbottabad, from 1st February 2016 to 31st January 2017. 210 patients undergoing cesarean section were included in this study. All the patients who participated in this study were categorized and further divided into two equal groups. Each group comprised 105 patients each through the process of block randomization. Patients in Group A were administered Amoxicillin 1000 mg and patients in group B were administered ceftriaxone 1000 mg for 48 hours following cesarean section patients were followed up on the 8thpost-op day for removal of stitches and wound examination. Results Wound infection was noted in 17 (8.1%) patients. 13 of which belonged to the Amoxicillin category. There was a statistically huge difference between the two groups regarding postoperative wound infection (p=0.023). Upon stratification of outcome variable with age and parity, the results were found to be statistically insignificant (p > 0.05). Conclusion The incidence of post-operative wound infection is minimal with the administration of ceftriaxone following a cesarean section.